Dinamika Tradisi Inung Tuak pada Masyarakat Kampung Adat Waerebo, NTT - Elfrida Mecik; Ida Bagus Oka Wedasantara; Aliffiati, Aliffiati (Institut Nalanda, 2025)
This study aims to examine the dynamics of the inung tuak tradition, or the custom of drinking palm wine, among the Waerebo Indigenous Community in East Nusa Tenggara as an integral part of Manggarai ethnic culture. The research employs a qualitative approach with data collected through participatory observation, in-depth interviews, and literature studies. The findings reveal that the inung tuak tradition holds strong social, spiritual, and symbolic functions in the community's life, both in customary rituals and everyday interactions. Furthermore, the growth of tourism has influenced the form and practice of this tradition while preserving its core cultural values. This tradition serves as a medium for intergenerational value transmission and symbolizes reverence for ancestors and a harmonious relationship with nature.